Online collaboration, teachers training and ICT in the classroom: a case study - Risoleta DE JESUS PINTO; Maria Luísa LEBRES AIRES (Ediciones Universidad de Salamanca, 2013)
ICT is changing not only ways of life, but also the individuals' minds and cultures of different social groups.  For these reason, it is supposed that schools appear as innovation centers focused on the network society. However, previous research accomplished under the Network of Municipal Observatories for Literacy and Digital Inclusion has revealed that despite teachers in primary schools acknowledge the importance of digital technologies and the Internet, they occasionally use these technologies, justifying this low level of use on a lack of pedagogical skills. Additionally, the single teacher in primary schools has led to cultures of professional isolation that hinder the dynamics of networking, a fundamental dimension to the promotion of digital literacy. Given these facts and the theoretical review about learning in virtual environments, we offered an online teachers training course about ICT to primary schools teachers, in Santarém, Portugal. The results enhance the positive value of joint dynamics among teachers, which contributes to their professional development, as well as leads to the inclusion of ICT in the classroom.